Histórias, memórias e saberes amazonenses: a escuta dos contos de tradição oral de moradores do município de Parintins (AM) - Barroso, Aline de Oliveira (Brasil, 2023)
The present study was driven by the concern to highlight the traditions of oral tales and record this knowledge led by residents of the municipality of Parintins (AM), constructing narratives, experiences and explanations of our Amazonian universe. Thus, the objectives of the study were outlined, in general to research on the tales of oral tradition recording memories and cultural knowledge of residents of the municipality of Parintins (AM), in order to: a) listen to and record the voices and memories of residents of the municipality of Parintins, valuing the tales of oral tradition; b) to evidence the traditional knowledge, stories and memories through the oral narratives of residents in Parintins (AM); c) and analyze the contribution of the contents that make up the tales of oral tradition for reflections, experiences and explanations of the knowledge of the Amazonian context. For this, a methodological path was traced based on a qualitative research, through the methodology of Oral History (MEIHY, 2005). We conducted the field research in 06 more traditional and old neighborhoods of the municipality of Parintins, using the oral history interview with 10 (ten) residents. Authors such as Bussatto (2012), Thompson (2002), Benjamin (1987), Estés (1998), Le Goff (1994), Bosi (1994); Loureiro (2003), Barbosa (2011) grounded the concepts and epistemological reflections of the research. The study raised theoretical reflections, records of oral narratives and analyses of the rich experiences of the meetings with the residents, protagonists of the research, whose shared knowledge aroused looks and readings about the imaginary, myths, legends, faith, beliefs, ethnic groups and community life.